Productivity forecast with digital greenhouse automation system for sustainable agriculture - ÇELEBİ, MEHMET FATİH; ERSOY, SEZGİN (My University, 2022)
Greenhouses are a popular agricultural production method by providing artificial climatic conditions. Providing optimum climatic conditions depends on the equipment of the greenhouse. Greenhouse equipment consists of systems such as heating, ventilation, shading, irrigation, and fertilization. In modern greenhouse cultivation, all these have become controllable with smart systems. These modern greenhouses, in other words smart greenhouses, can read the ambient conditions in real-time with their advanced sensor systems and enable processes such as irrigation, adjustment of ambient temperature, and ventilation to be carried out autonomously. In this study, the working principle, general structure, design, and types of equipment used in the greenhouse automation system are explained, and the system is designed and simulated on the Unity Engine.
Keywords: Makina Mühendisliği; Mühendislik ve Teknoloji; Mechanical Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Fizik Bilimleri; Computational Mechanics; Automotive Engineering; Physical Sciences; biomass; biorefinery; systems design; zero emissions